Implementation Of Event Management Website Using CodeIgniter Framework - Teo Rinaldi; Rahmad Budi Utomo; Rio Septian Hardinata (Sean Institute, 2021)
Event management is a part of organizing activities that are professionally, efficiently, effectively, and systematically. Event management includes concept planning, implementation of activities, and control over the expected organizers. The success of organizing events, it is necessary to have good event management. In order to have an information system that can assist in the implementation of the event. The event management information system that will be implemented utilizing web-based information technology, aims to facilitate the event organizing committee in processing event data, participant data, attendance data, and event activity reports. This event management information system uses the PHP programming language, MySQL as the database, and CodeIgniter as the framework. The method used in this research is the grounded method (grounded research), a prototype model uses for system development. The designed procedures include event publication procedures, registration, payment, and attendance. The result of this research is a web-based event management information system. The designed system, it is hoped that it can help the event committee solve problems that often occur and provide better procedures for participants and the organizing committee.